Video-Supported Problem-Based Learning for Deepening Science Concepts and Nurturing Environmental Care - Ni Nyoman Rediani; Pande Made Dharma Sanjaya; Novi Indriyani; Rezky Uspayanti; Dian Agustina Purwanto Wakerkwa (Universitas Pendidikan Ganesha, 2025)
Many prospective teacher education students still feel anxious or lack confidence when participating in science learning. This condition negatively affects their level of conceptual understanding as well as the development of their social attitudes. This study aims to analyze the impact of video-assisted Problem-Based Learning (PBL) on students’ science conceptual understanding and environmental awareness. In this study, data were collected using test and questionnaire methods. The research subjects consisted of 88 students. The test method was used to measure students’ conceptual understanding, while environmental attitudes were assessed using a questionnaire instrument. Data analysis was conducted using descriptive and inferential statistical approaches. The results indicate that there was an improvement in students’ science conceptual understanding and environmental attitudes after participating in video-assisted PBL learning. Furthermore, there were significant differences in science conceptual understanding and environmental attitudes between students who were taught using video-assisted PBL and those who were not. The difference in science conceptual understanding between the two groups reached 9.34, with the experimental group obtaining a higher mean score. In addition, there was a difference of 5.13 in environmental attitudes, with the experimental group demonstrating higher mean scores compared to the control group. Therefore, it can be concluded that the implementation of video-assisted PBL is effective in enhancing prospective teacher education students’ science conceptual understanding while simultaneously fostering environmental awareness.